Dictionary of Qur'anic Terms and Concepts - Mohamed Taher (International Institute of Islamic Thought, 1991)
A long-awaited Muslim source and a nonorientalist handy reference book, this glossary (a more appropriate title for this dictionary) of the Qur'an fills a major vacuum. To date, we had to rely solely on Penrice’s Dictionary and Glossary of the Qur'an. This process of generating sources (indexes, bibliographies, handbooks, dictionaries, glossaries, and the like) - a sole prerogative of the Western world-has recently been taken up by Muslims. A healthy trend in this regard is visible in the source under review. Though this book has covered mainly Qur’anic terms and concepts, it has admittedly entered into the field of non-Qur’anic terms. This extension of scope makes it more useful to the community of scholars and students of the Qur’an. As the author rightly mentions in his introduction: “In a few cases, the Arabic terms used are the ones that have become traditionally accepted, even though they do not occur in the Qur’an (i.e., wudu') or occur in it in a different sense (i.e. qadhf); these include, in one or two cases, words which for some technical reason are to be regarded as ‘extra-Qur‘anic’ even when words from the same root and with the same basic meaning occur in the Qur’an-i.e., bay'ah, though mubaya'ah (in perfect and imperfect forms, that is) occurs in the Qur'an” (pp. xiii-xiv). Mir has used the generally accepted meanings and notions in his scholarly work. His explanations and notes are interesting and meaningful. For instance, explaining the term “Median Community” or “Ummah Wasat,” he goes on to say that the title of ”Median Community” is not only a prerogative, but also carries with it a responsibility-the responsibility to stay on the median path and guide others to it (p. 132). Similarly, under the term “Repentance” we find “Adam, after he had sinned, repented and was forgiven by God (237). Thus, he was sent upon earth not to receive punishment for his disobedience, but in accordance with an already existing plan. Since Adam was forgiven, no original sin attaches to the human race” (p. 180). Similarly, we find at another place: “Din has four meanings: 1. Submission . . . 2. A system of beliefs . . . 3. Law . . . and 4. Recompense . . .” (p. 49) ...